Modal dispersion curves for annular waveguides with core cross section bounded by conducting and dielectric nonconcentric circles - Singh U.K.; Singh O.N. (My University, 2025)
We study the modal characteristics of a waveguide of annular cross section with nonconcentric circular boundaries. In this study, either both or one of the cladding regions is taken as highly conducting. The bipolar coordinate system is introduced for the analysis, and the characteristic equations are derived. Results show that the absence of concentricity of the two boundaries reduces the number of sustained modes. Dispersion curves show that two types of modes are propagated simultaneously through the waveguide in which either of the claddings is metallic. One type shows an anomalous dispersion behavior. For the waveguide with both of the boundaries conducting, dispersion curves have the expected shape as in the case of standard annular waveguides of concentric circular boundaries.